Laryngeal cancer risk and common single nucleotide polymorphisms in nucleotide excision repair pathway genes ERCC1, ERCC2, ERCC3, ERCC4, ERCC5 and XPA - Lu, Baocai; Li, Jing; Gao, Qingzu; Yu, Wenfa; Yang, Qinghui; Li, Xiaoyu (Gene, 2014)
Because the molecular mechanisms underlying the development of laryngeal cancer are not well understood, we conducted a case–control study to determine the association between eight common SNPs in NER pathway genes and risk of laryngeal cancer, and the association between genetic polymorphisms and environmental factors. A 1:1 matched case–control study of 176 cases and 176 controls was conducted. Laryngeal cancer cases were more likely to smoke and drink (all P values<0.05). Subjects with the ERCC1 rs11615 CC genotype and C allele had an increased risk of laryngeal cancer. Similarly, individuals with the ERCC5 rs17655 GG genotype and G allele had an increased risk of laryngeal cancer. Gene–gene interaction analysis showed that subjects carrying ERCC1 rs11615 C allele and XPG/ERCC5 rs17655 G allele had a greatly increased risk of breast cancer. Stratified analysis revealed that the interaction between polymorphisms of ERCC1 rs11615 and ERCC5 rs17655 and smoking on cancer risk was statistically significant, and ERCC1 rs11615 polymorphisms also had a significant interaction with drinking habit. In conclusion, our study suggests that ERCC1 rs11615 and ERCC5 rs17655 polymorphisms are associated with increased risk of laryngeal cancer, and that they confer more risk among smokers and drinkers. •ERCC1 rs11615 CC and C allele have an increased risk of laryngeal cancer.•ERCC5 rs17655 GG and G allele show a higher increased risk of laryngeal cancer.•RCC1 rs11615 C allele and ERCC5 rs17655 G allele have a greatly increased risk.•ERCC1 rs11615 and ERCC5 rs17655 have significantly interaction with smoking habit.•ERCC1 rs11615 polymorphisms have significantly interaction with drinking habit.